“Between a child who wants to tell and an adult who does not want to hear”. Arts Therapists’ Dilemmas in the Application of Arts Therapy with Children from Arab Society Who Suffered Abuse - MUSSA, AMANI (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Amani Mussa, “Between a child who wants to tell and an adult who does not want to hear”. Arts Therapists’ Dilemmas in the Application of Arts Therapy with Children from Arab Society Who Suffered Abuse. Interdisciplinary Contexts of Special Pedagogy, no. 25, Poznań 2019. Pp. 373-401. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2019.25.16. The Arab education system in Israel together with the ethics and legal regulations are found to indicate reports of maltreated and sexually abused children. The problem of viewed in this paper is connected with the reporting of children who had experienced maltreatment and sexual abuse. The article aspires to present the work and dilemmas of art therapists using arts therapy when working within educational and therapeutic frameworks in Israeli Arab society. Today, the field of arts therapy in the Arab society is in its initial stages in contrast to the seniority this field has gained in the Jewish society and more traditional therapies such as psychology and psychotherapy. In the Arab society, mental therapy is uncommon. The field of therapy as a whole is undeveloped and conducted secretly largely due to shame, stigma and prejudices associating mental therapy with mental illnesses or disorders (Masarwa & Bruno, 2018). Until recently, arts therapy has not been practiced at all in Israeli in the Arab society. In comparison to psychological treatment, arts therapy carries an extra value because of its non-verbal work methodology, and enables can the client to make projection and reduction of social and personal objections in face of the therapeutic process. In recent years, implementation of this field of knowledge has gained momentum in therapeutic frameworks in general and at schools in particular, slowly becoming an integral part of the education system. However, this field is still in its early stages and it is oriented towards special education students and those with special needs (Nachum, 2007; Moriah, 2000).